E-commerce Adoption and Consumer Behavior in the Post-Pandemic Era : a Case Study of Southeast Asia (Universitas Kristen Indonesia Toraja, 2024)
The COVID-19 pandemic accelerated e-commerce adoption across Southeast Asia, reshaping consumer behavior. This paper analyzes post-pandemic purchasing trends using case studies from Indonesia, Malaysia, and Vietnam. Key factors influencing consumer preferences, such as convenience, trust, and digital payment adoption, are identified to guide business strategies in the evolving digital economy.